SEHATI : Sosialisasi Pencegahan dan Aksi Penanganan Stunting di Negeri Hatalai, Kota Ambon - Ronald Darlly Hukubun; Laury Marcia Chara Huwae; Laura Bianca Sylvia Huwae; Joel Apriyanto Fejacreyo Huka (Universitas Maritim AMNI Semarang, 2024)
Stunting is a disorder of growth and development of children due to chronic malnutrition, repeated infections, and has an impact on children's cognitive abilities. SSGI in 2022 shows that the stunting prevalence rate in Indonesia reaches 21.6% with Ambon City reaching 20.9%, which is still far from the 2024 national prevalence target of 14%. This is triggered by risk factors that cause stunting, one of which is comprehension of stunting. Hatalai as one of the countries in Ambon City has a stunting prevalence rate of <-3SD which reaches 0%, in fact, it is not allowed to stand idly by. Prevention efforts are urgently needed to continue to maintain and support the reduction in the national stunting prevalence rate. One effective way is the socialization of education about stunting and the implementation of stunting handling actions. Community service is carried out with health education methods and is carried out in Hatalai Country and produces positive benefits for the community. The socialization carried out provides understanding to pregnant and lactating women related to stunting and its prevention, and stunting actions provide awareness of the importance of physical activity and the implementation of balanced nutrition guidelines as an effort to prevent and handle stunting.